Do the crime, do the time: juvenile criminals and adult justice in the American court system - Mays, G. Larry (Praeger, 2012)
"This book provides a fresh look at the way the United States is choosing to deal with some of the serious or persistent youth offenders: by transferring juvenile offenders to adult courts"--